2020
DOI: 10.18203/2320-1770.ijrcog20205268
|View full text |Cite
|
Sign up to set email alerts
|

Sudden bradycardia and impending cardiac arrest by intra-myometrial vasopressin in laparoscopic myomectomy: a case report and review of literature

Abstract: Vasopressin has long been used in myomectomy to decrease blood loss. Its efficacy is beyond doubt. But at the same time it is known to cause some of the serious cardiovascular side effects. We here report a case of severe bradycardia and impending cardiac arrest caused by intra-myometrial infiltration of 12 U of vasopressin and present a review of literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(16 reference statements)
0
1
0
Order By: Relevance
“… 7 , 8 Vasopressin has been widely available. However several related adverse effects have been reported particularly on the cardiovascular system 9 , 10 , 11 , 12 and the United States Food and Drug Administration has not approved the drug for this purpose. 13 A recent meta‐analysis of 26 clinical trials concluded that it was not yet clear which intervention was optimal.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Vasopressin has been widely available. However several related adverse effects have been reported particularly on the cardiovascular system 9 , 10 , 11 , 12 and the United States Food and Drug Administration has not approved the drug for this purpose. 13 A recent meta‐analysis of 26 clinical trials concluded that it was not yet clear which intervention was optimal.…”
Section: Introductionmentioning
confidence: 99%